A novel g-C3N4-nanosheets/Ni3V2O8 n-p heterojunction nanocomposite: A promising photocatalyst with enhanced photocatalytic degradation of tetracycline under visible light irradiation. (December 2022) - Almojil, Sattam Fahad; Almohana, Abdulaziz Ibrahim; Alali, Abdulrhman Fahmi; Chaturvedi, Rishabh; Mehrez, Sadok; Mohamed, Abdullah; Rashidi, Shima; Cao, Yan
Abstract: A photocatalytic system designed based on heterojunction formation can be successful in the degradation of pollutants by separating and transporting charge carriers. For this purpose, high performance g-C3 N4 -nanosheets/Ni3 V2 O8 n-p heterojunction with different weight percentages of Ni3 V2 O8 was achieved by calcination-hydrothermal method. Various descriptive properties including morphology, crystallinity, functional groups, optical interaction, elemental composition, electron-hole separation, and energy band structure were analyzed by SEM, TEM, HRTEM, XRD, FT-IR, UV–vis DRS, EDX, XPS, PL, EIS, photocurrent, and Mott-Schottky. Photocatalytic tests were performed by degrading tetracycline in the visible spectrum. The best efficiency is attributed to the g-C3 N4 -nanosheets/Ni3 V2 O8 (30%) nanocomposite, which can degrade 97.5% of tetracycline within 40 min. The effects of the amount of photocatalyst, initial concentration of TC and pH on the efficiency of tetracycline degradation were investigated and the optimal conditions were determined. The results show that n-p heterojunction formation with improving the separation and migration of charge carriers led to an increase in photocatalytic activity compared to g-C3 N4 -nanosheets and Ni3 V2 O8 . The obtained nanocomposite was recycled 4 times without significant loss of photocatalytic performance, which is a confirmation of the high stability of the photocatalyst. The results of trapping experiments and Mott-Schottky analysis were used to propose a possible mechanism by combining g-C3 N4 -nanosheets and Ni3 V2 O8 components with matching energy band structures. This paper presents an idea for fabricating g-C3 N4 -nanosheets-based heterogeneous photocatalysts for tetracycline degradation using visible spectrum light. Graphical abstract: Image 1 Highlights: High performance g-C3 N4 -nanosheets/Ni3 V2 O8 n-p heterojunction was achieved by calcination-hydrothermal method. The g-C3 N4 -nanosheets/Ni3 V2 O8 (30%) nanocomposite showed a highest rate constant (862 × 10 −4 min −1 ) for degradation of tetracycline. Construction of n-p heterojunction effectively inhibited the recombination of charge carriers.